Single-pion production in proton-proton collisions at 1.25 GeV: measurements by HADES and a PWA - Przygoda Witold (EPJ Web of Conferences, 2014)
We report on the single-pion production in proton-proton collisions at a kinetic energy of 1.25 GeV based on data measured with HADES. Exclusive channels npπ+ and ppπ0 were studied simultaneously. The parametrization of production cross sections of the one-pion final states by means of the resonance model has been obtained. Independently, the extraction of the leading partial waves in the data were analyzed within the framework of the partial wave analysis (PWA). Contributions for the production of ∆(1232) and N(1440) intermediate states have been deduced.